Hubungan Kontrol Diri dengan Kenakalan Remaja di Sekolah - Maiyulita, Ririn; Syukur, Yarmis (Lembaga Yasin AlSys, 2024)
Adolescence is a period of developmental transition between childhood and adulthood which generally begins at the age of 12 or 13 years and ends at the age of (late teens or early twenties). During this transition period, it is possible that a period of crisis will arise, which is characterized by a tendency for naughty or deviant behavior to emerge. One of the factors that influences juvenile delinquency is self-control. This research aims to describe the picture of student juvenile delinquency at school, describe student self-control and examine the relationship between self-control and juvenile delinquency at school. This research is a quantitative descriptive correlational type of research. The population of this research is students of SMP Negeri 1 Kubung, totaling 339 students enrolled in the 2023/2024 academic year. Sampling was determined using a purposive sampling technique with a sample size of 35 students. Data collection used a self-control questionnaire and a questionnaire on juvenile delinquency at school with a Likert scale model. The data was processed using percentage analysis techniques and to test the relationship between the two variables using the Pearson correlation product moment formula. The results of this research show that: (1) juvenile delinquency of students at SMP Negeri 1 Kubung is in the high category with a percentage of 53.94%, self-control of students at SMP Negeri 1 Kubung is in the low category with a percentage of 57.67%, (2) self-control students at SMP Negeri 1 Kubung are in the low category with a percentage of 57.67%, (3) there is a significant negative relationship between self-control and juvenile delinquency of -464 with a significance level of 0.005. A significant negative relationship means that the higher the student's self-control, the lower the student's delinquency. On the other hand, the lower the student's self-control, the higher the student's delinquency. The implications of the results of this research can be used as a guideline in providing guidance and counseling services in schools, especially in information services, group guidance services, group counseling services and individual counseling services in preventing juvenile delinquency at school.